The professional project of graphic designers and universities' visual identities. Issue 2 (19th July 2021) - Moldenæs, Turid; Pettersen, Hilde Marie
Abstract: Contrary to earlier research on why universities change their visual identities from traditional to more abstract ones, resting on a demand-side approach, we offer an explanation based on a supply-side approach. We argue that universities' change of visual identities toward abstract symbols reflects a professional logic shared by graphic designers and discuss the mechanisms and institutional agents that have fueled the professional project of graphic designers and the institutionalization of their professional logic. Simultaneously, we make visible the role of a professional group—the graphic designers—that have escaped the gaze of earlier organizational research.